From PICO to search terms on the internet: How to find relevant information? New coxibs: Do they have a better gastrointestihal safety? - Van Den Bruel, A; Boland, B; Vermeire, E; Buntinx, F; Aertgeerts, B (2005)
In the first article of this series, we have shown how to translate a clinical problem into a well bait question, by creating a PICO (Patient - Intervention - Comparison - Outcome). In this second article, we will explain how to transform the PICO in English search terms for use on the internet We use these terms in the different databases to find the answer to the following clinical problem: "In pstients aged 65 or over with hip ostesarthritis, and a history of peptic ulcer, is the risk of a new peptic ulcer less using a cos-2 inhibitor than with a classic nonsteroidal anti-inflammatory drug?".